Fundamentals of Entrepreneurship ENT300 Ice Sugarlicious! / Nur Affina Kiprawi... [et.al] - Kiprawi, Nur Affina; Ruzani, Nur Fatin Amira; Roslan, Nur Enn Shermaine; Abdul Rahim, Nur Farhan Asyikin (2015)
Basically, our target for the business is everyone which means who ever people that is afford to buy our ice-cream. However, the people who lied nearby Jalan Simpang Tiga, Kenyalang Park is our main target. Besides the people who lived in Jalan Tabuan is also our target. Our ice-cream which has many types of flavours with a colourful concept will make them interested to buy our ice-cream especially made for the kids and teenagers. Meanwhile, adults and elders may enjoy our ice-cream too as it is fat-free ice-cream. Ice Sugarlicious! is located opposite the Spring Shopping Mall and in the developing town that may attract all the shoppers there to come to our shop. Our business has a market capitalization of RM 100 000.